Turismo de megaeventos e planejamento regional: as contribuições de técnicas de big data no estudo da demanda turística recebida nos jogos olímpicos Rio 2016 - Minozzo, Daniele Solana (2024)
In recent decades, mega sporting events have been used as a tool for urban transformation and international promotion of the host cities. One of the objectives of international publicity carried out on these occasions is to increase the visibility of the tourism destination, and thus also increase the number of foreign tourists in the country. Although mega-events are often associated with international demand for tourism, indicators showed that the largest public received on these occasions is frequently composed of domestic tourists. This thesis is dedicated to the study of flow and accommodation data of the effective tourist demand received during The Olympic Games Rio 2016, the largest mega-event hosted in the period, which was considered a success in terms of attendance and revenue received. In this work, it was assessed how much of these positive tourism externalities, perceived in the tourist destination of the city of Rio de Janeiro during the 2016 Olympics, can be attributed to domestic tourism demand. The research was based on the division and comparison of data from the two groups of tourists that make up the total demand received, domestic and international. The data used was collected during the event in the city of Rio de Janeiro by municipal, state and federal public bodies, as well as trade associations in the tourism sector, which were later made available in demand books. The Mobile Data Analysis Report provided by the City of Rio de Janeiro was analyzed, based on information from tourists generated in big data, the comparison of this material with other references contributed to a broad perception of the composition of tourist demand for mega events, and to identify differences in behavior between international and domestic tourist groups at the time. The methodology used in the thesis serves the public authorities as an example for future analysis of demand data from tourist destinations, not limited to the reception of mega events. It is concluded that there was a “mega-event syndrome” at the Rio de Janeiro Olympic Games due to the overestimation of the increase in tourist flow in later periods. The results indicated the dependence of domestic demand on tourism in Brazil even after the 2013-2016 mega-event cycle. Domestic tourist groups also showed a better geographic distribution in the city during the Rio Olympics. While international groups registered a greater concentration in the Copacabana Cluster, there was a greater registration of domestic groups in the Barra Cluster and Maracanã Cluster. Among the 2016 Olympic legacies identified are the partnerships established by the city hall, between different spheres of power in investing in urban infrastructure, and public-private partnerships, in the application of data mining techniques and technologies that helped in managing the city’s flows in the Olympic period and influenced later initiatives around the world.